2005
DOI: 10.1007/s10578-005-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Effectiveness of Coping in Pediatric Patients

Abstract: Findings about the influence of coping on psychological adjustment in children with different medical conditions are inconsistent and often based on cross-sectional data. This prospective study evaluated the effect of various coping strategies on children's post-traumatic stress symptoms and behavioral problems 1 month and 1 year after an accidental injury or the diagnosis of a chronic disease in 161 pediatric patients 6-15 years of age. Only minor positive effects of coping on psychosocial adjustment were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 28 publications
4
43
0
2
Order By: Relevance
“…The design of seven studies (50%) was cross-sectional, but two of the six longitudinal studies reported relevant statistics only for the cross-sectional associations (Benore et al, 2008;Luberto et al, 2012) and one study did not clearly specify the time points used (Lyon et al, 2014). Thus, only four studies clearly reported on longitudinal associations, spanning a one-year (Zehnder et al, 2006), two-year (Reynolds, Mrug, Hensler, et al, 2014), and five-year (Reynolds, Mrug, Britton, et al, 2014) prospective periods and a three-year retrospective period (Grossoehme et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of seven studies (50%) was cross-sectional, but two of the six longitudinal studies reported relevant statistics only for the cross-sectional associations (Benore et al, 2008;Luberto et al, 2012) and one study did not clearly specify the time points used (Lyon et al, 2014). Thus, only four studies clearly reported on longitudinal associations, spanning a one-year (Zehnder et al, 2006), two-year (Reynolds, Mrug, Hensler, et al, 2014), and five-year (Reynolds, Mrug, Britton, et al, 2014) prospective periods and a three-year retrospective period (Grossoehme et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies developed or adapted existing questionnaires (with 12 and 24 items, respectively; Park & Nachman, 2010;Shelton, 2004); two used the average of self-developed two items (Landolt et al, 2002;Zehnder et al, 2006); and one study used a single item (Luberto et al, 2012). When reported, internal consistency of these measures was excellent for positive spiritual coping (Cronbach's α = .84 to .96) and acceptable for negative spiritual coping (α = .71 to .79).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 189 cancer patients in England, 35%, 31%, and 18% described opportunities for personal prayer, support from people of their faith, and support from a spiritual adviser as important needs, respectively. Finally, over three fifths of hospitalized children between the ages of eight and 16 in Switzerland said they asked God for help or prayed to God for comfort [17].…”
Section: Prevalence Of Religious Copingmentioning
confidence: 99%
“…Hollywell and Walker's [60] review of research on prayer suggested that studies typically find negative relationships between prayer and anxiety. Swiss children who asked God for help or prayed to God for comfort reported fewer posttraumatic stress symptoms during a follow-up assessment 11 months later [17]. In a longitudinal study of cardiac patients, positive religious coping was concurrently related to lower levels of anger coping; both positive religious coping and a composite measure of religious activities and self-rated religiousness were negatively related to hostility [10].…”
Section: Religious Coping Emotion and Healthmentioning
confidence: 99%